Hypocoagulability and Platelet Dysfunction Are Exacerbated by Synthetic Colloids in a Canine Hemorrhagic Shock Model - Boyd, Corrin J.; Claus, Melissa A.; Raisis, Anthea L.; Hosgood, Giselle; Sharp, Claire R.; Smart, Lisa (Frontiers in Veterinary Science, 2018)
Background: Hemorrhagic shock and volume replacement can alter coagulation. Synthetic colloids, hydroxyethyl starch (HES) and gelatin, may enhance hypocoagulability. Our primary objective was to describe the effect of four fluid products on coagulation in canine hemorrhagic shock. Our secondary objective was to compare measurements of coagulation during shock to baseline in all dogs. Methods: Anesthetized greyhounds subjected to atraumatic hemorrhage for 60 minutes were administered 20 mL kg-1 of either fresh whole blood (FWB), 6% HES 130/0.4, 4% succinylated gelatin (GELO), or 80 mL kg-1 of isotonic crystalloid over 20 minutes (n=6 per group). Platelet closure time (PCT), rotational thromboelastometry (ROTEM) and plasma coagulation assays were measured at baseline, end of hemorrhage (shock), and 40 (T60) and 160 (T180) minutes after study fluid. ROTEM parameters included clotting time (CT), clot formation time (CFT), alpha angle, maximum clot firmness (MCF), lysis index at 60 minutes (LI60) and thrombodynamic potential index (TPI) for INTEM, EXTEM, FIBTEM (MCF only) and APTEM (LI60 only) profiles. Plasma coagulation assays included prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen concentration and activities of factor VII (FVII), factor VIII (FVIII) and von Willebrand Factor antigen (vWF). Between-group differences were tested using linear mixed models with post hoc between-group comparisons (Bonferroni-Holm corrected). Differences between baseline and shock were tested using paired t-tests. Significance was set at P<0.05. Results: GELO showed longer PCT at T60, compared with FWB and CRYST, and at T180, compared with all other groups. HES showed longer EXTEM CT at T60, compared with all other groups. HES showed lower INTEM and EXTEM MCF at T60 and lower INTEM MCF at T180, compared with FWB. Some plasma coagulation assays showed greater hypocoagulability with HES. Comparing shock to baseline, EXTEM CT, INTEM CFT, EXTEM CFT, PT and FVIII significantly increased and PCT, INTEM CT, INTEM MCF, EXTEM MCF, EXTEM LI60, EXTEM TPI, FIBTEM MCF, APTT, fibrinogen, FVII and vWF significantly decreased. Conclusions: In dogs with hemorrhagic shock, volume replacement with GELO caused mild platelet dysfunction and HES was associated with coagulation changes consistent with hypocoagulability, beyond effects of hemodilution. Shock alone produced some evidence of hypocoagulability.